Das grönländische Inlandeis nach neuen Feststellungen - Loewe, Fritz (ERDKUNDE, 1964)
Some references to important publications on the physico-geographical conditions of the Greenland ice sheet are given. The height of the ice surface is generally found by barometric measurements. This method encounters on an ice sheet special difficulties; the same applies to normal trigonometrical survey methods. Recently an extremely accurate profil across the ice sheet has been established by levelling. The mean height of the surface is 2100-2150 m (7000 ft), the greatest height close to 3300 m (11,000 ft). The thickness of the ice has been measured by seismic and gravimetric methods at many places. The mean thickness is 1500-1600 m (5000 ft), with a maximum of 3400 m (11,150 ft). In the central parts the rock base is at or near sea level. Since 1949 several meteorological stations have been operating or are still working on the ice sheet. Additionally at many places the mean annual temperature has been determined from the firn temperature at a depth of a few meters. The central parts north of 71° N have a mean annual temperature slightly below -30° C (-20° F). Com pared with its surroundings at the same level the ice cap is a cold region. This is mainly due to the small absorption of solar radiation by the uncontaminated snow surface. The average annual intake of short wave radiation is estimated at 21 kcal/qcm, the loss of longwave radiation at -26 kcal/qcm; a deficit of -5 kcal/qcm per year results. This heat loss at the surface is, however, only a small fraction of the radiative losses of the arctic atmosphere; hence the presence of the Greenland ice sheet is not of great importance for the general circulation of the northern hemisphere. Precipitation cannot be reliably measured, but differs generally little from the more easily determined accumulation. The most frequent wind on the ice sheet is, even with small inclination of the surface, a gravity wind roughly down the slope. The direction of the strongest winds with the heaviest snow drift differs frequently from that of the prevailing wind. The border between ice and firn at the surface at the end of the summer is higher than the level at which ablation equals accumulation. The ice substance at the surface shows a systematic change of facies from the outer to the inner parts of the ice sheet. The accumulation is fairly well known from measurements at stakes and in pits. A zone of maximum accumulation occurs at heights of 2000? 2500 m. The mean net accumulation per year in the area of prevailing accumulation is 34 cm of water; the mean net ablation in the lower parts is 110 cm. The total ablation by runoff of melt water is much smaller than the total accumulation. Iceberg formation nearly accounts for the difference. The east coast is much less productive of icebergs than the west coast. The Greenland ice sheet is presently not markedly diminishing; it may be stable or even slightly increasing. The motions of the open ice sheet are still almost unknown; this applies still more to the motions at depth. Recently 100 points on the ice sheet have been very accurately fixed by tellurometer. Several deep pits and drill holes have confirmed that the temperature of the ice remains unchanged or even decreases down to 400 m. This can be explained by the heat fluxes and transports in a materially and thermically stable glacier, possibly in combination with a recent change of climate.